2019
DOI: 10.1016/s2214-109x(18)30526-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel vital sign device on maternal mortality and morbidity in low-resource settings: a pragmatic, stepped-wedge, cluster-randomised controlled trial

Abstract: Summary Background In 2015, an estimated 303 000 women died in pregnancy and childbirth. Obstetric haemorrhage, sepsis, and hypertensive disorders of pregnancy account for more than 50% of maternal deaths worldwide. There are effective treatments for these pregnancy complications, but they require early detection by measurement of vital signs and timely administration to save lives. The primary aim of this trial was to determine whether implementation of the CRADLE Vital Sign Alert an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 34 publications
2
48
1
Order By: Relevance
“…This is a secondary analysis of a pragmatic, stepped-wedge cluster randomised controlled trial of the introduction of the Community Blood Pressure Monitoring in Rural Africa: Detection of Underlying Pre-Eclampsia (CRADLE) intervention into routine maternity care in ten regions across Zimbabwe, Zambia, Sierra Leone, Malawi, Ethiopia, Uganda, Haiti and India over 20 months, from 1 April 2016 to 30 November 2017 (International Standard Randomised Controlled Trial Number, ISCRTN: 41244132). 7,8 The CRADLE intervention consisted of the CRADLE Vital Sign Alert, 7,9 a validated device that accurately measures blood pressure (BP) and heart rate and calculates the shock index, displaying the results on a traffic light early warning system, and a simple education package on how to use the device and respond to abnormal vital signs. 10,11 This intervention was compared with routine maternity care using local management guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…This is a secondary analysis of a pragmatic, stepped-wedge cluster randomised controlled trial of the introduction of the Community Blood Pressure Monitoring in Rural Africa: Detection of Underlying Pre-Eclampsia (CRADLE) intervention into routine maternity care in ten regions across Zimbabwe, Zambia, Sierra Leone, Malawi, Ethiopia, Uganda, Haiti and India over 20 months, from 1 April 2016 to 30 November 2017 (International Standard Randomised Controlled Trial Number, ISCRTN: 41244132). 7,8 The CRADLE intervention consisted of the CRADLE Vital Sign Alert, 7,9 a validated device that accurately measures blood pressure (BP) and heart rate and calculates the shock index, displaying the results on a traffic light early warning system, and a simple education package on how to use the device and respond to abnormal vital signs. 10,11 This intervention was compared with routine maternity care using local management guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The READS computer system has been used at Kitovu to collect vital signs at the bedside since 2016, and for this study an electrocardiograph was used to assess heart rate, a computer application to accurately determine respiratory rate measured over 60 seconds, and a well-validated blood pressure machine to record blood pressure. [20][21][22] Since our patients were younger than most patient populations in the developed world, it is not surprising that adding age weighting to MEWS did not improve its performance since the weightings for age would have applied to so few patients. 4 The mean temperatures and systolic blood pressures of patients who lived and died were identical; changes in temperature may be intermittent and change in blood pressure may be a late sign of deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility studies have shown high levels of acceptability by Community Health Workers (CHWs) in Nigeria, Mozambique, Zimbabwe, Ethiopia and India (18,19). A large stepped-wedge cluster-randomized controlled trial across 10 LMICs was; however, unable to demonstrate impact on the primary composite outcomes of maternal mortality and morbidity (20). This may be due, in part, to insufficient power and sample size, and significant variations between clusters (20).…”
Section: Community-level Interventions For High-risk Pregnanciesmentioning
confidence: 99%
“…A large stepped-wedge cluster-randomized controlled trial across 10 LMICs was; however, unable to demonstrate impact on the primary composite outcomes of maternal mortality and morbidity (20). This may be due, in part, to insufficient power and sample size, and significant variations between clusters (20). Low cost urinalysis devices for proteinuria detection have also been developed and piloted (21)(22)(23), although evidence of impact on clinical endpoints is lacking.…”
Section: Community-level Interventions For High-risk Pregnanciesmentioning
confidence: 99%